MON-666 Glucokinase Within the Hypothalamic Paraventricular Nucleus Is Important in GLP-1 Release - Ratnasabapathy, Risheka (J Endocr Soc, 2020)
When glucose is taken orally more insulin is secreted than when glucose is injected directly into the bloodstream. This is known as the incretin effect. Glucagon like peptide 1 (GLP-1) is one of the hormones responsible for this effect. GLP-1 is released from enteroendocrine L-cells in the gut in response to oral glucose intake. GLP-1 increases insulin synthesis and secretion. Release of GLP-1 is thought to be solely dependent upon gastrointestinal tract mechanisms. Here we identify a brain mechanism via the hypothalamic paraventricular nucleus (PVN) which is important in the release of GLP-1 in response to oral glucose. The role of the paraventricular nucleus in glucose homeostasis was previously unknown. We found that a glucokinase dependent glucose sensing mechanism in the PVN works in conjunction with the gut to regulate GLP-1 release. We show that increasing expression of GK (sense GK, sGK) into the PVN improves glucose tolerance (15 minutes glucose: GFP: 8.93±0.27mmol/L, n=11; sGK: 7.72±0.22mmol/L, n=12; p<0.01 and 15 minutes insulin GFP: 2.84±0.14mmol/L, n=11; sGK: 3.73±0.27mmol/L, n=12; p<0.01) and increases GLP-1 release in response to oral glucose (GFP: 6.16±0.18mmol/L, n=11; sGK: 6.90±0.26mmol/L, n=12; p<0.01). On the contrary decreasing expression of GK (antisense GK, asGK) in the PVN worsens glucose tolerance (30 minutes glucose: GFP: 8.22±0.28mmol/L; asGK: 9.46±0.24mmol/L, n=8; p<0.01 and 15 minutes insulin: GFP: 4.07±0.37mmol/L; asGK: 2.25±0.17mmol/L, n=8; p<0.001) and blunts (GLP-1 release 30 minutes GLP-1: GFP: 6.93±0.25pMol/L, n=8; p<0.01 asGK: 5.47±0.13pMol/L, n=8; p<0.001). Our results demonstrate that glucosensitive GK neurones in the PVN, are important to the response to oral glucose and the subsequent release of GLP-1.